2016
DOI: 10.1371/journal.pone.0156282
|View full text |Cite
|
Sign up to set email alerts
|

Knee Joint Loads and Surrounding Muscle Forces during Stair Ascent in Patients with Total Knee Replacement

Abstract: Total knee replacement (TKR) is commonly used to correct end-stage knee osteoarthritis. Unfortunately, difficulty with stair climbing often persists and prolongs the challenges of TKR patents. Complete understanding of loading at the knee is of great interest in order to aid patient populations, implant manufacturers, rehabilitation, and future healthcare research. Musculoskeletal modeling and simulation approximates joint loading and corresponding muscle forces during a movement. The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Kutzner et al [42] measured knee joint contact forces during various daily living activities and found that resultant forces lay typically in the range of 220% and 350% of the participant’s bodyweight. Similar values have also been reported in other in-vivo studies using instrumented implants [43,44,45]. The present study estimated approximately 2 bodyweights during sit to stand, which had the lowest contact forces of the tasks estimated; while approximately 4 bodyweights were measured during stair descent, which had the highest contact forces of the tasks estimated.…”
Section: Discussionsupporting
confidence: 90%
“…Kutzner et al [42] measured knee joint contact forces during various daily living activities and found that resultant forces lay typically in the range of 220% and 350% of the participant’s bodyweight. Similar values have also been reported in other in-vivo studies using instrumented implants [43,44,45]. The present study estimated approximately 2 bodyweights during sit to stand, which had the lowest contact forces of the tasks estimated; while approximately 4 bodyweights were measured during stair descent, which had the highest contact forces of the tasks estimated.…”
Section: Discussionsupporting
confidence: 90%
“…Lastly, while GRFs are a convenient variable to estimate the loading and moments experienced by the leg, 18 the true indicator of knee joint loading would be the internal joint reaction forces (which can be calculated through musculoskeletal modeling). 20 Although GRFs are correlated with modeling-based knee joint reaction forces, 26 future studies could be more exact if they examine the internal joint reaction forces.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rasnick et al predicted the knee joint stair ascent forces for five patients implanted with a posterior stabilized TKR [33]. Average resultant peak contact forces were 2.8 BW and 3.9 BW for the peaks in the first and second half of the stair ascent activity cycle.…”
Section: Discussionmentioning
confidence: 99%